2011
DOI: 10.1016/j.semnephrol.2011.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Approaches to Patients With Polycystic Kidney Disease

Abstract: Imaging is an important approach to diagnosis, monitoring and predicting outcomes for patients with Autosomal Dominant polycystic Kidney Disease (ADPKD). This paper reviews three common clinical imaging techniques, ultrasonography, computed tomography (CT), magnetic resonance imaging (MRI) and their role in management of ADPKD. Ultrasonographic criteria for diagnosis in children and adults are reviewed. Total kidney volume (TKV), as measured by MRI, is suggested as important potential marker to determine disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 32 publications
2
57
1
2
Order By: Relevance
“…In ADPKD, the interobserver variability was high, and there were about 300 and 700 ml differences in KV measured by ultrasonography and MRI, within the lower and higher volume range, respectively [22]. These results showed that the ultrasonographic KV measurement in ADPKD lacked precision [22,23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ADPKD, the interobserver variability was high, and there were about 300 and 700 ml differences in KV measured by ultrasonography and MRI, within the lower and higher volume range, respectively [22]. These results showed that the ultrasonographic KV measurement in ADPKD lacked precision [22,23]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the disadvantages of CT include ionized radiation and the use of a nephrotoxic contrast medium. Given these limitations, CT has a limited role in longitudinal imaging of ADPKD patients [23]. …”
Section: Discussionmentioning
confidence: 99%
“…It also incorporates caTissue [76], caArray [77], NBIA [67] and AIM UML models, associated common data elements (CDEs) and underlying NCI Thesaurus (NCIT) and other ontology concepts. We use NCIT [78] and Metathesaurus with concepts from BRIDG [79] and LS DAM models and other standardized domain ontologies such as from the Open Biological and Biomedical Ontologies Foundry [80]. We incorporate non-imaging data such as clinical outcomes by mapping to concepts from the Patient Outcome Data Service [81].…”
Section: Development Roadmapmentioning
confidence: 99%
“…Imaging modalities such as ultrasound (US), computed tomography (CT), and magnetic resonance imaging (MRI) are used to monitor disease progression (8). Clinical studies utilize total kidney volume (TKV) measured by MRI as an image-based biomarker to follow the progression of ADPKD since larger TKVs have been shown to correlate with worse prognosis in ADPKD in both human (9), and murine studies (10).…”
Section: Introductionmentioning
confidence: 99%